2021
DOI: 10.1002/app.51780
|View full text |Cite
|
Sign up to set email alerts
|

Konjac glucomannan: A review of structure, physicochemical properties, and wound dressing applications

Abstract: Natural bio‐based materials used in wound dressings have been continuously developed in recent years, and have certain advantages in water retention, biocompatibility, and therapeutic properties. Konjac glucomannan (KGM) is a kind of plant polysaccharide with good cell compatibility and gel properties. Various gels obtained by modification of KGM through physical and chemical methods have great application potential in wound excipients. In the past few years, various KGM‐based wound barrier materials such as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 133 publications
0
20
0
Order By: Relevance
“…Previous studies have confirmed that the abundant hydroxyl groups on PVA can spontaneously form hydrogen bonds with water molecules, thereby immobilizing the water molecules. In addition, KGM is also considered to be a good water-retaining material, which further increases the water absorption properties of the fibrous membranes. , Due to good water absorption, the fibrous membrane can absorb water in the blood at the start of the process, increasing the concentration of coagulation factors and promoting blood coagulation. , At the same time, it can also maintain a moist environment at the wound, which will be beneficial for the repair and regeneration of the wound tissue. , All these results have confirmed that PG-PVA/KGM is a good candidate for wound dressing toward the accelerating of wound tissue regeneration.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have confirmed that the abundant hydroxyl groups on PVA can spontaneously form hydrogen bonds with water molecules, thereby immobilizing the water molecules. In addition, KGM is also considered to be a good water-retaining material, which further increases the water absorption properties of the fibrous membranes. , Due to good water absorption, the fibrous membrane can absorb water in the blood at the start of the process, increasing the concentration of coagulation factors and promoting blood coagulation. , At the same time, it can also maintain a moist environment at the wound, which will be beneficial for the repair and regeneration of the wound tissue. , All these results have confirmed that PG-PVA/KGM is a good candidate for wound dressing toward the accelerating of wound tissue regeneration.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, KGM is also considered to be a good water-retaining material, which further increases the water absorption properties of the fibrous membranes. 36,37 Due to good water absorption, the fibrous membrane can absorb water in the blood at the start of the process, increasing the concentration of coagulation factors and promoting blood coagulation. 38,39 At the same time, it can also maintain a moist environment at the wound, which will be beneficial for the repair and regeneration of the wound tissue.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Konjac glucomannan (KGM) is a hydrophilic biomolecule derived from konjac tubers and consists of glucose and mannose linked by β-1,4-glucosidic bonds [ 1 , 2 ]. KGM can be used as a stabilizer or a gelling and thickening agent in the food industry due to its excellent properties in gel-forming, film-forming and water-holding capacity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Konjac glucomannan (KGM) is a non-ionic water-soluble polysaccharide composed of D-glucose and D-mannose through β-1, 4, and 4 pyranoside bonds. It is mainly derived from konjac tubers and is a kind of abundant natural renewable resource [ 1 , 2 , 3 , 4 ]. KGM cannot be degraded in the upper gastrointestinal tract but can only be degraded by β-mannanase or β-glucosidase in the colon.…”
Section: Introductionmentioning
confidence: 99%